A new graphic user interface to the South Pole information system - Biagioni, Stefania; Carlesi, Carlo; Salvetti, Ovidio; Spoto, Vincenzo (1997)
An integrated multi-disciplinary information system, known as the South Pole Information System (SPIS), has been developed within the framework of the Italian Programme for Research in the Antarctic promoted by ENEA (National Agency for Alternative Energy). The system consists of a series of heterogeneous data_banks sited in Local Centres, geographically distributed throughout the Italian territory, each one dedicated to a specific theme. The main objective of the South Pole System has been to make all the data and information concerning the Italian Antarctic expeditions available to the scientific community, through the creation of a series of specific networked Local Centres (LC). The system thus provides: i) local and remote access to all the information; ii) compatibility with international standards; iii) homogeneous user-friendly interfaces; iv) the possibility to perform comparative and interdisciplinary searches.